EFFICIENCY AND SAFETY OF ROBOT-ASSISTED THORACOSCOPIC LOBECTOMIES WHEN MANAGING PULMONARYTUBERCULOSIS - P. K. Yablonsky; G. G. Kudryashov; I. V. Vasilyev; A. O. Avetisyan; A. D. Ushkov; O. P. Sokolova (Туберкулез и болезни лёгких)
Currently, there are no doubts about the relevance of surgery as a part of integral treatment. However, minimally invasive surgeries for treatment of pulmonary tuberculosis are rarely used due to post-inflammatory changes in the pleural space and lung root. And outcomes of robot-assisted lobectomies in pulmonary tuberculosis patients have never been investigated.The objective of the study: to investigate the efficiency and safety of robot-assisted surgeries in pulmonary tuberculosis patients.Subjects and methods. Since May 2013, 56 patients suffering from focal unilateral pulmonary tuberculosis were enrolled into a prospective study, after having an adequate course of anti-tuberculosis chemotherapy. At the moment of surgery, bacillary excretion persisted in 32% of patients, and 90.5% of patients had cavities.Results. All patients had robot-assisted lobectomies using the surgical system of Da Vinci Si. The average time of surgery made 174 minutes (90-380 minutes), the blood loss made 82 ml (10-500 ml). In 2 (3%) patients, a robot-assisted access was converted into lateral thoracotomy. The frequency of post-operative surgical complications made 25% [6].Conclusion. High clinical efficiency and safety are associated with robot-assisted lobectomies as a part of the integral treatment of pulmonary tuberculosis patients.